2025 Kunming Manifesto: Agrobiodiversity for people and planet - Alliance of Bioversity International and CIAT; Chinese Academy of Agricultural Sciences (CAAS); Yunnan Agricultural University (2025)
Agrobiodiversity underpins our agri-food systems. Conserving, sustainably using, and investing in our planet’s natural wealth of agricultural biodiversity is essential to achieve food security, climate resilience, and environmental sustainability. The currently used food systems, predominantly driven by industrial agriculture, have hindered the achievements in these important areas. While 2025's State of Food and Nutrition in the World (SOFI) reportsError! Bookmark not defined. point to a global decrease in hunger in 2024, a staggering 673 million people faced hunger during the year. The report showed that in Africa and West Asia, hunger worsened. Moreover, 2.3 billion people experienced moderate to severe food insecurity in 2024, 683 million more than in 2015, the year global leaders adopted the Sustainable Development Agenda. The agenda includes achieving zero hunger by 2030. Without a radical and transformative shift in the way we produce, distribute, and consume food, five years from now hundreds of millions of people will still be hungry. The Kunming Manifesto is a result of the 3rd International Agrobiodiversity Congress, held in May 2025 in Kunming, China. The congress attended by experts, practitioners, and decision-makers from around the world to consolidate evidence demonstrated that increased sustainable use of agrobiodiversity is one of our most effective strategies to eradicate hunger, adapt to climate change, reduce soil degradation and loss of biodiversity in production landscapes. The scientific findings, case studies, and best practices shared in Kunming showed that agrobiodiversity has the potential to significantly contribute to goals set forth by the three Rio Conventions on climate, biodiversity and desertification. Unfortunately, agrobiodiversity is still largely on the sidelines of these existential global discussions. The Manifesto compiles insights from the Kunming congress to bring the case for agrobiodiversity to an international audience, aiming to catalyze global action based on evidence and expertise. By "experts," we are not solely referring to global leaders in academia, development and policymaking. Experts include the Indigenous peoples and local rural communities, whose in-depth understanding and generational custodianship of agrobiodiversity merit greater inclusion – and leadership roles – in embedding agrobiodiversity into the food system mainstream. Their expertise, often overlooked in global discussions on the world's future, can meaningfully contribute to creating the policies, markets, and financial incentives needed for agrobiodiversity to flourish. The agrobiodiversity conservation, use, and success stories are largely the domain of women, who are often the most marginalized in marginalized groups. In tandem with greater inclusion, unlocking agrobiodiversity's potential to help solve the world's greatest challenges requires transformative intervention by governments around the world. This includes repurposing agricultural subsidies, enacting policies to support the seed production and distribution systems and embedding agrobiodiversity in the global fora that works to mitigate climate change, reverse biodiversity loss, control desertification, and eliminate hunger. As the Kunming Congress’s six key topics in this manifesto demonstrate, agrobiodiversity's benefits are tangible and will repay greater investment many times over. The conclusions call for urgent actions based on the evidence that the conservation and use of agrobiodiversity is inextricably linked to the health of people and the planet they live on.